Optimal Power Flow with Integrated Large Scale PV Systems: Case of the Algerian solar field - Mallem, Aicha; Boudebbouz, Omar (IAES Indonesian Section, 2024)
The integration of large-scale solar-photovoltaic generation in the traditional power system complicates the optimal power flow (OPF) problem formulation. In the present paper, the OPF based on the quadratic and cubic fuel cost functions integrating solar energy potential of the south of Algeria is presented. Solar energy has a stochastic behavior described in the proposed methodology by the Beta probability distribution function (βPDF). The corresponding objective functions consider the penalty and reserve costs of large-scale solar-photovoltaic generations. The proposed OPF is solved by particle swarm optimization (PSO) algorithm. Computer simulations have been performed on an Algerian 59 bus test system considering some candidates solar energy source emplacements. The comparison between OPF solutions based on the two aforementioned cost functions has been established. The cubic fuel cost function case shows more environmental pollution reduction as well as satisfying interconnected power demands. Thanks to the PSO algorithm properties used for the OPF resolution, the Algerian solar field seems to be a good opportunity for large-scale solarphotovoltaic generation installations in an oligopolistic and eco-friendly sense.